(untitled) (International journal of artificial intelligence, 2025)
The development of the education sector in rural areas is crucial for ensuring equitable access to quality education. This paper explores the challenges faced by rural communities, including inadequate infrastructure, teacher shortages, and limited technological resources. Additionally, it examines policy interventions and innovative solutions such as digital learning, teacher training programs, and community engagement strategies. By addressing these issues, governments and stakeholders can enhance educational opportunities, reduce disparities, and contribute to sustainable socio-economic development.